2018
DOI: 10.3329/bjar.v43i4.39158
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis studyin maize inbreds throughout diallel mating design

Abstract: Combining ability effects were estimated for grain yield and some other important agronomic traits of maize in a 7×7 diallel analysis excluding reciprocals. The variances for general combining ability (GCA) were found significant for yield, days to pollen shedding, days to silking and ear height while it was found non-significant for plant height and number of kernels/ear. Non-significant general combining ability (GCA) variance for plant height and number of kernels/ear indicates that these two traits were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
2
5
1
Order By: Relevance
“…This finding pointed out that dominant or non-additive types of gene activity predominate in these genotypes. This result is in contrast with Tilahun et al (2017) and Karim et al (2018) who reported prevalence of additive gene action for all the traits except days to silking. Dominant or nonadditive gene action was also reported by Yerva et al (2016), Kumar et al (2017), Hassan et al (2019) and Arunkumar et al (2022).…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…This finding pointed out that dominant or non-additive types of gene activity predominate in these genotypes. This result is in contrast with Tilahun et al (2017) and Karim et al (2018) who reported prevalence of additive gene action for all the traits except days to silking. Dominant or nonadditive gene action was also reported by Yerva et al (2016), Kumar et al (2017), Hassan et al (2019) and Arunkumar et al (2022).…”
Section: Resultscontrasting
confidence: 98%
“…The parents involved in theses crosses also showed good general combining ability effects and performed substantially better in specific crosses. E1-Shamarka et al (2015), Basser et al (2021) and Arunkumar et al (2022) also reported desirable significant negative sca effects for earliness in their experiment while Karim et al (2018) reported non-significant sca effect for days to 50% silking Most of these crosses have at least one parent with low gca effects. Significant negative sca effects for PH were observed in five crosses, namely Q5 x Q7 (-39.47), Q5 x Q8 (-23.20), Q6 x Q7(-13.57) Q1 x Q3 (-12.94) and Q3 x Q4 (-10.54), and for EH four crosses, namely Q6 x Q7(-29.50), Q5 x Q7(-26..43), Q5 x Q8 (-18.77) and Q2 x Q4 (-8.87) showed significant negative sca effects.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, over check, HQPM-5 a total of 12 hybrids recorded significant standard heterosis in desirable positive direction in leaf area index. These results were in line with the findings of Mohammed and Yousif (2020) and Karim, A.N.M.S et al [28]. The highest grain yield was recorded in the hybrid P 5 X P 7 (188.41 q/ha) and this hybrid differed significantly over the best check for seed index, cob length, plant height and starch content.…”
Section: Heterosissupporting
confidence: 91%
“…To develop highly productive multi-nutrient maize hybrids, breeders should know the GCA and SCA of inbred lines, since they both indicate the breeding value of inbred lines in hybrid combinations ( Karim et al., 2018 ). GCA has been defined by Sprague and Tatum (1942) as the average performance of the inbred line based on its performance in crosses with other inbred lines.…”
Section: Introductionmentioning
confidence: 99%